Thermally conductive composition, method for producing laminate, and laminate

By using a combination of agglomeration reactant and metal filler in the thermally conductive material to form a multi-layer structure of thermally conductive composition, the problem of poor thermal conductivity of traditional thermal conductive materials on silicon substrates is solved, and a combination of low thermal impedance and high thermal conductivity is achieved.

JP2025037423APending Publication Date: 2025-03-18DEXERIALS CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023144352
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Traditional thermally conductive materials have problems with high thermal impedance and poor thermal conductivity when in contact with silicon substrates, especially in the formation of a continuous thermally conductive particle network.

Method used

Using a thermal conductivity composition comprising a coagulation reactant and a metal filler, the combination of the first thermal conductivity layer formed by the coagulation reaction and the second thermal conductivity layer is reduced to the contact thermal resistance of the silicon substrate and to improve the thermal conductivity.

Benefits of technology

It achieves low thermal impedance, excellent thermal conductivity and good adhesion to the silicon substrate, ensuring efficient thermal management.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037423000018
    Figure 2025037423000018
  • Figure 2025037423000019
    Figure 2025037423000019
  • Figure 2025037423000020
    Figure 2025037423000020
Patent Text Reader

Abstract

To provide a thermally conductive composition capable of reducing contact resistance with a silicon substrate while ensuring excellent adhesion, high thermal conductivity, and low thermal resistance.SOLUTION: A thermally conductive composition comprises a condensation reaction product and a metal filler, wherein the condensation reaction product results from the condensation of a partial hydrolysate of an alkyl silicate and an epoxy-functional silane coupling agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a thermally conductive composition, a method for producing a laminate, and a laminate. [Background technology]

[0002] In large scale integration (LSI) and the like in various electronic devices, if the LSI itself is exposed to high temperatures for a long period of time due to heat generation from the elements used, this may lead to malfunction or failure. For this reason, thermally conductive materials are widely used to prevent the temperature of LSIs and the like from rising. The thermally conductive materials can prevent the temperature of the equipment from rising by diffusing the heat generated by the elements or by transmitting it to a heat dissipation member for dissipation outside the system, such as the atmosphere.

[0003] When metals or ceramics are used as such thermal conductive materials, there are problems such as difficulty in reducing weight, poor processability, and low flexibility. Therefore, various thermal conductive materials have been proposed that use polymeric materials such as resin or rubber as a base material. For example, materials in which fibrous carbon particles are dispersed in resin are used.

[0004] Known examples of thermally conductive members made of polymeric materials include inter-surface thermally conductive sheets, which are polymeric sheets based on sheet-shaped polymeric materials and transmit heat in a direction perpendicular to the main surface of the polymeric sheet (inter-surface direction, i.e., sheet thickness direction).Specific examples include thermal interface materials (TIM1), which fill minute gaps between a heat source such as an LSI and a heat sink to allow heat to flow smoothly between the two.

[0005] For example, a porous silver sheet has been proposed which is a free-standing film formed of porous silver, which is a porous body of silver, and has a density of 40 to 72 volume %, in which the average crystal grain size of the silver crystals of the porous silver is 1.7 to 2.6 μm, and which has a bending modulus of elasticity of 16 to 24 GPa, a maximum bending strength of 100 MPa or more, and a breaking bending strain of 1.3% or more as obtained in a three-point bending test at 25°C (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2016-169411 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, in the conventional technology described in Patent Document 1, when a silicon substrate is used as the base material, not only does thermal resistance occur at the contact point with the silicon substrate, but the formation of a network (continuous phase) by thermally conductive particles is insufficient, making it difficult to obtain high thermal conductivity.

[0008] The present invention aims to solve the above-mentioned problems in the prior art and to achieve the following objectives: That is, the present invention aims to provide a thermally conductive composition that can reduce the contact resistance with a silicon substrate and achieve excellent adhesion, high thermal conductivity, and low thermal resistance. [Means for solving the problem]

[0009] The means for solving the above problems are as follows. <1> Contains a condensation reaction product and a metal filler, The thermally conductive composition is characterized in that the condensation reaction product is a condensation reaction product obtained by partially hydrolyzing an alkyl silicate represented by the following general formula (1) and a coupling agent represented by the following general formula (2): [ka] In the general formula (1), R 1 represents an alkyl group, and n represents a positive number. [ka] In the general formula (2), R2 represents an alkyl group, Y represents a substituent containing an epoxy group, p represents an integer of 0 to 3, and q represents a positive number. <2> R in the general formula (1) 1 is a methyl group or an ethyl group. <1> The thermally conductive composition according to claim 1, <3> R in the general formula (2) 2 is a methyl group or an ethyl group. <1> from <2> The thermally conductive composition according to any one of claims 1 to 5, <4> The compound according to the above, wherein Y in the general formula (2) is a glycidoxy group. <1> from <3> The thermally conductive composition according to any one of claims 1 to 5, <5> The metal filler includes at least one of silver nanowires, gold nanowires, copper nanowires, and aluminum nanowires. <1> from <4> The thermally conductive composition according to any one of claims 1 to 5, <6> On a silicon substrate, <1> from <4> The present invention relates to a method for producing a laminate, the method comprising the step of applying the thermally conductive composition according to any one of the above to form a first thermally conductive layer. <7> applying a second thermally conductive composition onto the first thermally conductive layer, the second thermally conductive composition including a second curing component, a second curing agent, second thermally conductive particles, and low melting point metal particles; and heating the applied second thermally conductive composition. <6> 2. A method for producing the laminate according to claim 1 . <8> A silicon substrate; A first thermally conductive layer provided on the silicon substrate, the first thermally conductive layer containing a condensation reaction product and a metal filler; The laminate is characterized in that the condensation reaction product is a condensation reaction product obtained by partially hydrolyzing an alkyl silicate represented by the following general formula (1) and a coupling agent represented by the following general formula (2): [ka] In the general formula (1), R 1 represents an alkyl group, and n represents a positive number. [ka] In the general formula (2), R 2 represents an alkyl group, Y represents a substituent containing an epoxy group, p represents an integer of 0 to 3, and q represents a positive number. <9> The heat conductive layer further comprises a second heat conductive layer provided on the first heat conductive layer, the second heat conductive layer including a second hardening component, a second hardening agent, second heat conductive particles, and a low melting point metal. <8> 1. The laminate according to claim 1 . <10> The thermal conductivity is 30W / (m K) or more. <9> 1. The laminate according to claim 1 . Effect of the Invention

[0010] According to the present invention, it is possible to solve the above-mentioned problems in the conventional art, achieve the above-mentioned object, and provide a thermally conductive composition that can reduce the contact resistance with a silicon substrate and realize excellent adhesion, high thermal conductivity, and low thermal resistance. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic view showing an example of a laminate according to the first embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing an example of a process of a method for producing a laminate according to the second embodiment. [Diagram 3] FIG. 3 is a schematic diagram showing an example of a laminate according to the second embodiment. [Figure 4] FIG. 4 is a schematic cross-sectional view showing an example of a heat dissipation structure having the laminate of the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] (Thermal conductive composition) The thermally conductive composition of the present invention (sometimes referred to as the "first thermally conductive composition") contains a condensation reaction product and a metal filler, and may further contain other components as necessary. <Condensation reaction product> The condensation reaction product is a condensation reaction product obtained by partially hydrolyzing an alkyl silicate represented by the following general formula (1) and a coupling agent represented by the following general formula (2).

[0013] [ka] In the general formula (1), R 1 represents an alkyl group, and n represents a positive number.

[0014] [ka] In the general formula (2), R 2 represents an alkyl group, Y represents a substituent containing an epoxy group, p represents an integer of 0 to 3, and q represents a positive number.

[0015] -Alkyl silicates and partial hydrolyzates- The alkyl silicate is a compound represented by the following general formula (1). The partial hydrolyzate is a product obtained by partially hydrolyzing the alkyl silicate.

[0016] [ka] In the general formula (1), R 1 represents an alkyl group, and n represents a positive number.

[0017] In the general formula (1), each R 1 The alkyl group is not particularly limited and can be appropriately selected depending on the purpose. Examples of the alkyl group include linear or branched alkyl groups having 1 to 10 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an s-butyl group, an i-butyl group, a t-butyl group, and an n-hexyl group. Of these, a methyl group or an ethyl group is preferred.

[0018] In the general formula (1), n ​​is not particularly limited and can be appropriately selected depending on the purpose.

[0019] As the alkyl silicate, a commercially available product can be used. For example, Methyl Silicate 51 (R 1 = methyl group, n ≒ 4), methyl silicate 53A (R 1 = methyl group, n ≒ 7), etc. The descriptions in parentheses indicate the respective definitions of general formula (1).

[0020] -Coupling agent- The coupling agent is a compound represented by the following general formula (2).

[0021] [ka] In the general formula (2), R 2 represents an alkyl group, Y represents a substituent containing an epoxy group, p represents an integer of 0 to 3, and q represents a positive number.

[0022] In the general formula (2), each R 2 The alkyl group is not particularly limited and can be appropriately selected depending on the purpose. Examples of the alkyl group include linear or branched alkyl groups having 1 to 10 carbon atoms, such as a methyl group, an ethyl group, an n-propyl group, an i-propyl group, an n-butyl group, an s-butyl group, an i-butyl group, a t-butyl group, and an n-hexyl group. Of these, a methyl group or an ethyl group is preferred.

[0023] In the general formula (2), Y is not particularly limited as long as it is a substituent containing an epoxy group, and may be appropriately selected depending on the purpose. Examples of Y include a hydrocarbon group having an epoxy group and an oxygen atom (e.g., a glycidoxy group), a cyclic hydrocarbon group having an epoxy group (e.g., a monovalent group of 1,2-epoxycyclohexane), and a substituent combining a cyclic hydrocarbon group having an epoxy group and a hydrocarbon group having an oxygen atom. Among these, an epoxy group and a hydrocarbon group having an oxygen atom are preferred, and a glycidoxy group is more preferred.

[0024] In the general formula (1), q is not particularly limited and can be appropriately selected depending on the purpose.

[0025] As the coupling agent, a commercially available product can be used. For example, SILQUEST A-187 (R 2 = methyl group, Y = glycidoxy group, p = 0, q = 3), SILQUEST A-186(R 2 = methyl group, Y = monovalent group of 1,2-epoxycyclohexane, p = 0, q = 2). The descriptions in parentheses indicate the respective definitions of general formula (2).

[0026] [Method for producing condensation reaction product] The method for producing the condensation reaction product is not particularly limited and can be appropriately selected depending on the purpose. For example, the following methods can be mentioned. -Preparation of partial hydrolyzate of alkyl silicate- In a reaction vessel equipped with a nitrogen inlet tube, a thermometer, and a stirrer, a solvent such as ethanol and sulfuric acid are added to the alkyl silicate represented by the general formula (1) and stirred. After stirring is completed, an evaporator is used to distill off the methanol produced by hydrolysis and the added solvent from the reaction product. The resulting distillation residue is passed through a cation exchange resin column to remove excess sulfuric acid. A solvent such as isopropyl alcohol is added little by little to the resulting partial hydrolyzate while stirring is continued. This allows the partial hydrolyzate of the alkyl silicate to be obtained as a solution.

[0027] -Preparation of condensation reaction product- The prepared solution of the partial hydrolyzate of alkyl silicate is put into a reaction vessel equipped with a stirrer, and the silane coupling agent represented by the general formula (2) is gradually added while stirring. By this condensation reaction, the condensation reaction product can be obtained as a solution.

[0028] <Metal filler> The metal filler is preferably a metal nanowire, and is preferably at least one of silver nanowires, gold nanowires, copper nanowires, and aluminum nanowires.

[0029] The metal nanowires are not particularly limited as long as they are wire-shaped metal with a nanoscale thickness and can be appropriately selected depending on the purpose, but it is preferable that the average wire diameter is 10 nm to 100 nm and the average wire length is 5 μm to 20 μm.

[0030] The content of the metal filler is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 5 mass % or more and 50 mass % or less, and more preferably 10 mass % or more and 30 mass % or less, relative to the total amount of the thermally conductive composition. When the content of the metal filler is from 5% by mass to 50% by mass, the thermally conductive composition can achieve high thermal conductivity and low thermal resistance.

[0031] <Other ingredients> The thermally conductive composition may contain other components as long as the effects of the present invention are not impaired. The other components are not particularly limited and can be appropriately selected depending on the purpose. Examples of the other components include thermally conductive particles other than metals (e.g., aluminum nitride, alumina, carbon fibers, etc.), additives (e.g., antioxidants, ultraviolet absorbers, curing accelerators, silane coupling agents, leveling agents, flame retardants, etc.), and the like.

[0032] The thermally conductive composition can be prepared by uniformly mixing the condensation reaction product, the metal filler, and other components as required by a conventional method.

[0033] The thermally conductive composition may be either a thermally conductive sheet in sheet form or a thermally conductive paste in paste form (also called a thermally conductive adhesive or a thermally conductive grease). Among these, a thermally conductive sheet is preferred from the viewpoint of ease of handling, and a thermally conductive paste is preferred from the viewpoint of cost.

[0034] (Method of manufacturing laminate) The method for producing a laminate of the present invention includes a first applying step, and preferably includes a second applying step, and further includes other steps as necessary.

[0035] [Method for manufacturing the laminate of the first embodiment] In one embodiment, the method for manufacturing the laminate includes a first application step, thereby making it possible to manufacture a laminate (a laminate of the first embodiment) having a silicon substrate and a first thermally conductive layer provided on the silicon substrate. This allows the contact resistance at the interface of the silicon substrate to be significantly reduced, and when an additional thermally conductive layer is provided, a laminate can be produced that can achieve excellent adhesion, high thermal conductivity, and low thermal resistance.

[0036] [Method for manufacturing the laminate according to the second embodiment] In another embodiment, the method for manufacturing the laminate includes a first application step, a second application step, and a heating step, thereby making it possible to manufacture a laminate (a laminate of the second embodiment) having a silicon substrate, a first thermally conductive layer provided on the silicon substrate, and a second thermally conductive layer provided on the first thermally conductive layer. This makes it possible to manufacture a laminate that can reduce the contact resistance with the silicon substrate and achieve excellent adhesion, high thermal conductivity, and low thermal resistance.

[0037] <First application step> The first application step is a step of applying the above-mentioned thermally conductive composition of the present invention (also referred to as the "first thermally conductive composition") onto the silicon substrate to form a first thermally conductive layer. The condensation reaction product, metal filler, and other components contained in the thermally conductive composition can be appropriately selected from those described in the thermally conductive composition of this embodiment.

[0038] Examples of methods for applying the first thermally conductive composition to the substrate include spin coating, inkjet coating, blade coating, gravure coating, gravure offset coating, bar coating, roll coating, knife coating, air knife coating, comma coating, U comma coating, AKKU coating, smoothing coating, microgravure coating, reverse roll coating, four-roll coating, five-roll coating, dip coating, curtain coating, slide coating, and die coating. The first thermally conductive composition in a sheet form may be applied onto the silicon substrate by means of transfer or the like.

[0039] -Silicon substrate- The shape, structure, size, material, etc. of the silicon substrate are not particularly limited and can be appropriately selected depending on the purpose. Examples of the shape of the substrate include a plate shape, a sheet shape, etc. Examples of the structure of the substrate include a single-layer structure, a laminated structure, etc. The size of the substrate can be appropriately selected depending on the application, etc.

[0040] The average thickness of the silicon substrate is not particularly limited and can be appropriately selected depending on the purpose. The silicon base material may be the heat generating body (electronic component) itself in the heat dissipation structure.

[0041] <Second applying step> The second applying step is a step of applying a second thermally conductive composition onto the first thermally conductive layer.

[0042] Examples of methods for applying the second thermally conductive composition to the substrate include spin coating, inkjet coating, blade coating, gravure coating, gravure offset coating, bar coating, roll coating, knife coating, air knife coating, comma coating, U comma coating, AKKU coating, smoothing coating, microgravure coating, reverse roll coating, four-roll coating, five-roll coating, dip coating, curtain coating, slide coating, and die coating. The second thermally conductive composition in a sheet form may be applied onto the substrate by means of transfer or the like.

[0043] <Heating process> The heating step is a step of heating the applied second thermally conductive composition, thereby forming a second thermally conductive layer on the first thermally conductive layer.

[0044] The heating conditions are not particularly limited as long as the curing component and the curing agent contained in the second thermally conductive composition react with each other to cure, and can be appropriately selected depending on the purpose. For example, the heating conditions are preferably 120°C to 190°C for 1 minute to 30 minutes, and more preferably 140°C to 170°C for 1 minute to 10 minutes.

[0045] By applying a second thermally conductive composition onto the first thermally conductive layer and then performing a heating step, the adhesiveness of the resulting first thermally conductive layer and second thermally conductive layer can be improved. In addition, the flux activity of the curing agent is expressed in the subsequent heating step, and the wettability between the molten low-melting point metal and the second thermally conductive particles can be improved.

[0046] -Second thermally conductive composition- The second thermally conductive composition contains a second curing component, a second curing agent, second thermally conductive particles, and low-melting point metal particles, and preferably contains a specific polymer, and further contains other components as necessary.

[0047] -Second hardening component- The second curing component preferably contains at least one of an oxetane compound and an epoxy resin, and more preferably contains an oxetane compound and an epoxy resin.

[0048] -Oxirane ring compounds- The oxirane ring compound is a compound having an oxirane ring, and examples thereof include epoxy resins. The epoxy resin is not particularly limited and can be appropriately selected depending on the purpose. Examples of the epoxy resin include glycidyl ether type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, bisphenol A type epoxy resins, trisphenol type epoxy resins, tetraphenol type epoxy resins, phenol-xylylene type epoxy resins, naphthol-xylylene type epoxy resins, phenol-naphthol type epoxy resins, phenol-dicyclopentadiene type epoxy resins, alicyclic epoxy resins, and aliphatic epoxy resins. These may be used alone or in combination of two or more.

[0049] -Oxetane compounds- The oxetane compound is a compound having an oxetanyl group, and may be an aliphatic compound, an alicyclic compound, or an aromatic compound. The oxetane compound may be a monofunctional oxetane compound having only one oxetanyl group, or a polyfunctional oxetane compound having two or more oxetanyl groups.

[0050] The oxetane compound is not particularly limited and can be appropriately selected depending on the purpose. Examples of the oxetane compound include 3,7-bis(3-oxetanyl)-5-oxa-nonane, 1,4-bis[(3-ethyl-3-oxetanylmethoxy)methyl]benzene, 1,2-bis[(3-ethyl-3-oxetanylmethoxy)methyl]ethane, 1,3-bis[(3-ethyl-3-oxetanylmethoxy)methyl]propane, ethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, triethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, tetraethylene glycol bis(3-ethyl-3-oxetanylmethyl)ether, 1,4-bis(3-ethyl-3-oxetanylmeth- oxy)butane, 1,6-bis(3-ethyl-3-oxetanylmethoxy)hexane, 3-ethyl-3-(phenoxy)methyloxetane, 3-ethyl-3-(cyclohexyloxymethyl)oxetane, 3-ethyl-3-(2-ethylhexyloxymethyl)oxetane, 3-ethyl-3-hydroxymethyloxetane, 3-ethyl-3-(chloromethyl)oxetane, 3-ethyl-3{[(3-ethyloxetan-3-yl)methoxy]methyl}oxetane, xylylene bisoxetane, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP), isophthalic acid bis[(3-ethyl-3-oxetanyl)methyl]ester (OXIPA), and the like. These may be used alone or in combination of two or more.

[0051] As the oxetane compound, commercially available products can be used. Examples of the commercially available products include the "ARON OXETANE (registered trademark)" series sold by Toagosei Co., Ltd. and the "ETERNACOLL (registered trademark)" series sold by Ube Industries, Ltd.

[0052] Among the oxirane ring compounds and oxetane compounds, glycidyl ether type epoxy resins, phenol novolac type epoxy resins, cresol novolac type epoxy resins, phenol-dicyclopentadiene type epoxy resins, bisphenol A type epoxy resins, aliphatic epoxy resins, 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl (OXBP), and isophthalic acid bis[(3-ethyl-3-oxetanyl)methyl]ester (OXIPA) are preferred.

[0053] The content of the curing component is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.5% by volume or more and 60% by volume or less based on the total amount of the thermally conductive composition.

[0054] <Hardening agent> The curing agent is a curing agent corresponding to the curing component, and examples thereof include polyaddition type curing agents such as polyfunctional carboxylic acid, acid anhydride type curing agent, aliphatic amine type curing agent, aromatic amine type curing agent (e.g., imidazole type curing agent), phenol type curing agent, and mercaptan type curing agent, and catalyst type curing agent such as imidazole. These may be used alone or in combination of two or more.

[0055] Among these, polyfunctional carboxylic acids are preferred, and polyfunctional carboxylic acids represented by at least one of the following general formula (I) and general formula (II) are more preferred.

[0056] [ka] In the general formula (I), R1 to R3 each independently represent a hydrogen atom, an alkyl group, or a caprolactone skeleton, R4 represents a hydrogen atom or an alkyl group which may be substituted with a hydroxyl group, and R5 represents an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 to 3 carbon atoms.

[0057] [ka] In the general formula (II), R1 and R2 each independently represent a hydrogen atom, an alkyl group, or a caprolactone skeleton. R4 and R6 each independently represent a hydrogen atom or an alkyl group which may be substituted with a hydroxyl group. R5 represents an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 to 3 carbon atoms.

[0058] The alkyl group in R1 to R3 in the general formula (I) and R1 and R2 in the general formula (II) is preferably an alkyl group having 1 to 10 carbon atoms, and examples thereof include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a hexyl group, a heptyl group, an octyl group, a 2-ethylhexyl group, a tert-octyl group, and a cyclohexyl group. The caprolactone skeleton in R1 to R3 in the general formula (I) and R1 and R2 in the general formula (II) is represented by the following general formula (i). [ka] In the general formula (i), n represents an integer of 1 or more, and preferably an integer of 1 to 10. m represents an integer of 2 or more, and preferably an integer of 2 to 5.

[0059] Examples of the alkyl group which may be substituted with a hydroxyl group in R4 and R6 include a methyl group, an ethyl group, a propyl group, -(CH2)-OH, -(CH2)2-OH, and -(CH2)3-OH.

[0060] Examples of the alkyl group having 1 to 3 carbon atoms for R5 include a methyl group, an ethyl group, a propyl group, and an isopropyl group. Examples of the alkenyl group having 2 to 3 carbon atoms for R5 include a vinyl group, a 1-propenyl group, and an allyl group (2-propenyl group). R5 is preferably either an alkyl group having 2 to 3 carbon atoms or an alkenyl group having 2 carbon atoms, from the viewpoint of combining excellent flux activity and curability.

[0061] The polyfunctional carboxylic acid represented by at least one of the general formula (I) and the general formula (II) can be synthesized by reacting a specific acid anhydride with a specific polyfunctional alcohol, as described below.

[0062] [Method of producing polyfunctional carboxylic acid] The method for producing the polyfunctional carboxylic acid includes a step of esterifying an acid anhydride with a polyfunctional alcohol, and further includes other steps as necessary. The esterification reaction between the acid anhydride and the polyfunctional alcohol is not particularly limited and can be appropriately selected depending on the purpose.

[0063] Examples of the acid anhydride include succinic anhydride, glutaric anhydride, maleic anhydride, phthalic anhydride, benzoic anhydride, oxalic anhydride, etc. These may be used alone or in combination of two or more. Among these, succinic anhydride, glutaric anhydride, and maleic anhydride are preferred.

[0064] The polyfunctional alcohol is preferably difunctional or more, more preferably difunctional or more and tetrafunctional or less. Examples of the polyfunctional alcohol include caprolactone derivatives, glycerin, ethylene glycol, and propylene glycol. These may be used alone or in combination of two or more. Of these, caprolactone derivatives and glycerin are preferred.

[0065] The caprolactone derivatives include compounds having a caprolactone skeleton represented by the general formula (i) above. As the caprolactone derivative, commercially available products can be used, and examples of the commercially available products include PLACCEL 205, PLACCEL 205U, PLACCEL 303, and PLACCEL 410 (all manufactured by Daicel Corporation).

[0066] An example of an esterification reaction between a specific acid anhydride and a trifunctional alcohol is shown below. [ka] In the above reaction formula, R1 to R3 represent a hydrogen atom, an alkyl group, or a caprolactone skeleton, R4 represents a hydrogen atom or an alkyl group which may be substituted with a hydroxyl group, and R5 represents an alkyl group having 1 to 3 carbon atoms or an alkenyl group having 2 to 3 carbon atoms.

[0067] The other steps are not particularly limited and can be appropriately selected depending on the purpose. For example, a concentration step, a separation and purification step, etc. can be mentioned.

[0068] The polyfunctional carboxylic acid represented by at least one of the general formulas (I) and (II) can achieve both a good flux effect and a good function as a curing agent. That is, the polyfunctional carboxylic acid represented by at least one of the general formulas (I) and (II) is liquid from room temperature to high temperature, and does not react during film formation, so that it can improve the wettability of the coating liquid. When heated in stages, it exerts the effect of a flux by the first heating stage, and then has a heat curing start switch function that starts curing by the curing components that were mixed together by the second heating stage. The heating temperature in the first stage is preferably 120°C to 150°C, for example. The heating temperature in the second stage is preferably 150°C to 190°C, for example.

[0069] The polyfunctional carboxylic acid is preferably liquid at 25°C and 150°C. Here, being liquid means having fluidity that allows application. The fact that the polyfunctional carboxylic acid is liquid at 25° C. and 150° C. can be confirmed, for example, by visually confirming the fluidity at 25° C. (room temperature) and by the presence or absence of an absorption peak up to 150° C. by DSC. The molecular weight of the polyfunctional carboxylic acid is preferably 800 g / mol or less, more preferably 400 g / mol or more and 700 g / mol or less, in view of being liquid. The molecular weight of the polyfunctional carboxylic acid can be measured, for example, by Shodex (registered trademark) GPC-101 (a product of Showa Denko K.K.).

[0070] The polyfunctional carboxylic acid is a curing agent having flux activity. By the first heating step, the polyfunctional carboxylic acid has flux activity, and therefore the wettability of the molten low-melting point metal to the second thermally conductive particles contained in the second thermally conductive composition can be improved. Then, by a second stage of heating, the polyfunctional carboxylic acid can cure the curing component in the second heat conductive layer.

[0071] The acid anhydride-based curing agent is preferred in that, when the curing component is an epoxy resin, no gas is generated during thermal curing, a long pot life can be achieved when mixed with the epoxy resin, and a good balance can be achieved between the electrical properties, chemical properties, and mechanical properties of the resulting cured product. Examples of the acid anhydride curing agent include cyclohexane-1,2-dicarboxylic anhydride, monoacid anhydrides of tricarboxylic acids, etc. Examples of the monoacid anhydrides of tricarboxylic acids include cyclohexane-1,2,4-tricarboxylic-1,2-acid anhydride, etc.

[0072] The curing agent preferably has flux activity from the viewpoint of improving the wettability of the molten low-melting point metal particles to the thermally conductive particles. Examples of methods for making the curing agent exhibit flux activity include methods of introducing protonic acid groups such as carboxyl groups, sulfonyl groups, and phosphoric acid groups into the curing agent by known methods. Among these, it is preferable to introduce a carboxyl group from the viewpoint of reactivity with the epoxy resin or oxetane compound as the curing component, and examples thereof include polycarboxylic acids containing a carboxyl group such as glutaric acid and succinic acid. The curing agent may also be glutaric anhydride or a compound modified from succinic anhydride, or a metal salt of a polycarboxylic acid such as silver glutarate.

[0073] The content of the curing agent is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 0.1 vol.% to 30 vol.%, more preferably from 0.5 vol.% to 20 vol.%, and even more preferably from 1 vol.% to 15 vol.%, based on the total amount of the thermally conductive composition.

[0074] -Second thermally conductive particle- The second thermally conductive particles are preferably at least any one of copper particles, silver-coated particles, and silver particles, and more preferably silver-coated particles. Examples of the silver-coated particles include silver-coated copper particles, silver-coated nickel particles, and silver-coated aluminum particles. The shape of the second thermally conductive particles is not particularly limited and can be appropriately selected depending on the purpose. Examples of the shape include spherical, flat, granular, and acicular shapes.

[0075] The volume average particle diameter of the second thermally conductive particles is preferably 1 μm or more and 100 μm or less, more preferably 5 μm or more and 70 μm or less, and even more preferably 5 μm or more and 50 μm or less. When the volume average particle diameter of the second thermally conductive particles is 1 μm or more and 100 μm or less, excellent thermal conductivity can be achieved. The volume average particle size of the second thermally conductive particles can be measured in the same manner as the volume average particle size of the metal filler.

[0076] -Low melting point metal- The low melting point metal means the low melting point metal particles and the low melting point metal formed by melting and solidifying the low melting point metal particles. As the low melting point metal particles, solder particles as specified in JIS Z3282-1999 are preferably used.

[0077] Examples of the solder particles include Sn-Pb solder particles, Pb-Sn-Sb solder particles, Sn-Sb solder particles, Sn-Pb-Bi solder particles, Sn-Bi solder particles, Sn-Bi-Ag solder particles, Sn-Cu solder particles, Sn-Pb-Cu solder particles, Sn-In solder particles, Sn-Ag solder particles, Sn-Pb-Ag solder particles, Pb-Ag solder particles, Sn-Ag-Cu solder particles, etc. These may be used alone or in combination of two or more. Among these, solder particles containing Sn and at least one selected from Bi, Ag, Cu, and In are preferred, Sn-Bi based solder particles, Sn-Bi-Ag based solder particles, Sn-Ag-Cu based solder particles, and Sn-In based solder particles are more preferred, and Sn-Bi based solder particles containing Sn and Bi are even more preferred.

[0078] The shape of the low melting point metal particles is not particularly limited and may be appropriately selected depending on the purpose. Examples of the shape include spherical, flat, granular, and acicular shapes. The melting point of the low-melting-point metal particles is preferably 100°C or higher and 250°C or lower, and more preferably 120°C or higher and 200°C or lower.

[0079] The melting point of the low-melting point metal particles is preferably lower than the heating temperature in the heating step. This allows the formation of a second thermally conductive layer in which a network (continuous metal phase) is formed by the molten low-melting-point metal via the second thermally conductive particles during the curing of the second thermally conductive composition, thus realizing a laminate with excellent heat resistance, thermal conductivity, and adhesiveness.

[0080] The volume average particle diameter of the low-melting metal particles is preferably 10 μm or less, more preferably 1 μm or more and 7 μm or less. When the volume average particle diameter of the low-melting metal particles is 10 μm or less, the volume ratio of the low-melting metal particles to the second thermal conductive particles can be reduced, and high thermal conductivity and low thermal resistance of the second thermal conductive layer can be achieved. The volume average particle size of the low-melting point metal particles can be measured in the same manner as the volume average particle size of the metal filler.

[0081] The volume average particle size of the second thermally conductive particles is larger than that of the low-melting-point metal particles, and the volume average particle size ratio (α / β) of the second thermally conductive particles α to the low-melting-point metal particles β is preferably 1.5 or more. The upper limit of the volume average particle size ratio (α / β) is preferably 10 or less. By using low-melting point metal particles having a smaller volume average particle size than the second thermally conductive particles, the second thermally conductive particles become the main component in the second thermally conductive composition, and the low-melting point metal particles present between the second thermally conductive particles and the second thermally conductive particles melt when heated and alloy with the second thermally conductive particles to form a network, thereby achieving high thermal conductivity and low thermal resistance.

[0082] In the second thermally conductive composition for forming the second thermally conductive layer, the volume ratio (α / β) of the second thermally conductive particles α to the low-melting point metal particles β is preferably at least 1, more preferably at least 1.5. The upper limit of the volume ratio (α / β) is preferably at most 4, more preferably at most 3.

[0083] <Specific polymer> The thermally conductive composition preferably contains a specific polymer in order to impart flexibility and sheetability. As the specific polymer, a polymer having at least one structure selected from a phenoxy structure, a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyalkylene structure, a polyalkyleneoxy structure, a polyisoprene structure, a polyisobutylene structure, a polyamide structure, and a polycarbonate structure in the molecule is used.

[0084] Examples of the specific polymer include a phenoxy structure such as bisphenol A type and bisphenol F type, a polybutadiene structure such as polybutadiene and hydrogenated polybutadiene, a polysiloxane structure such as silicone rubber, a poly(meth)acrylate structure, a polyalkylene structure (preferably a polyalkylene structure having 2 to 15 carbon atoms, more preferably a polyalkylene structure having 3 to 10 carbon atoms, and even more preferably a polyalkylene structure having 5 to 6 carbon atoms), a polyalkyleneoxy structure (preferably a polyalkyleneoxy structure having 2 to 15 carbon atoms, more preferably a polyalkyleneoxy structure having 3 to 10 carbon atoms), and It is preferable that the polyalkyleneoxy structure has at least one structure selected from the group consisting of a polyalkyleneoxy structure having 5 to 6 carbon atoms, and more preferable that the polyalkyleneoxy structure has at least one structure selected from the group consisting of a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure, it is preferable that the polyalkyleneoxy structure has at least one structure selected from the group consisting of a phenoxy structure, a polybutadiene structure, a polysiloxane structure, a poly(meth)acrylate structure, a polyisoprene structure, a polyisobutylene structure, and a polycarbonate structure, and it is more preferable that the polyalkyleneoxy structure has at least one structure selected from the group consisting of a phenoxy structure, a polybutadiene structure, a polyisoprene structure, and a polycarbonate structure.

[0085] The specific polymer preferably has a high molecular weight in order to exhibit flexibility. The number average molecular weight (Mn) of the specific polymer is preferably 1,000 or more and 1,000,000 or less, and more preferably 5,000 or more and 900,000 or less. The number average molecular weight (Mn) is a polystyrene-equivalent number average molecular weight measured using GPC (gel permeation chromatography).

[0086] The specific polymer is preferably selected from polymers having a glass transition temperature (Tg) of 25°C or lower and polymers that are liquid at 25°C in order to exhibit flexibility. The glass transition temperature (Tg) of the polymer having a glass transition temperature of 25° C. or lower is preferably 20° C. or lower, more preferably 15° C. or lower. There is no particular restriction on the lower limit of the glass transition temperature, and it can be appropriately selected depending on the purpose, but it is preferably −15° C. or higher. As the polymer that is liquid at 25°C, a polymer that is liquid at 20°C or less is preferable, and a polymer that is liquid at 15°C or less is more preferable.

[0087] From the viewpoint of improving the mechanical strength of the cured product, the specific polymer preferably has a functional group capable of reacting with the curing component. The functional group capable of reacting with the curing component also includes a functional group that appears upon heating. The functional group capable of reacting with the curing component is, for example, one or more functional groups selected from the group consisting of a hydroxy group, a carboxy group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, and a urethane group. Among these, the functional group is preferably a hydroxy group, an acid anhydride group, a phenolic hydroxyl group, an epoxy group, an isocyanate group, or a urethane group, and more preferably a hydroxy group, an acid anhydride group, a phenolic hydroxyl group, or an epoxy group.

[0088] The content of the specific polymer is preferably 1 vol. % or more and 50 vol. % or less, more preferably 1 vol. % or more and 30 vol. % or less, and even more preferably 1 vol. % or more and 20 vol. % or less, based on the total amount of the second thermally conductive composition.

[0089] <Other processes> The other steps are not particularly limited and may be appropriately selected depending on the purpose. For example, a protective layer forming step, an opposing substrate laminating step, and the like may be included.

[0090] (Laminate) The laminate of the present invention comprises a silicon substrate and a first thermally conductive layer, and preferably further comprises a second thermally conductive layer, and may further comprise an opposing substrate and other members as necessary.

[0091] [Laminate of the first embodiment] In one embodiment, the laminate (sometimes referred to as a "first laminate") includes a silicon substrate and a first thermally conductive layer provided on the silicon substrate. The first thermally conductive layer contains a condensation reaction product and a metal filler.

[0092] The laminate of the first embodiment can be suitably produced by the method for producing a laminate of the first embodiment. According to the laminate of the first embodiment, the contact resistance at the interface of the silicon substrate can be significantly reduced, and when an additional thermally conductive layer is provided, excellent adhesion, high thermal conductivity, and low thermal resistance can be achieved.

[0093] [Laminate of the second embodiment] In another embodiment, the stack includes a silicon substrate, a first thermally conductive layer disposed on the silicon substrate, and a second thermally conductive layer disposed on the first thermally conductive layer. The second thermally conductive layer contains a second hardening component, a second hardening agent, second thermally conductive particles, and a low-melting point metal, and may further contain other components as required. Here, the low melting point metal refers to the low melting point metal particles and the low melting point metal formed by melting and solidifying the low melting point metal particles.

[0094] The laminate of the second embodiment can be suitably produced by the method for producing a laminate of the second embodiment. The laminate of the second embodiment further includes a second thermally conductive layer having a low melting point metal, which is different from the laminate of the first embodiment, and thus can achieve a higher heat dissipation effect (higher thermal conductivity). Preferably, a thermal conductivity of 30 W / (m K) or more can be achieved.

[0095] <Silicon substrate> The silicon substrate can be appropriately selected from the items explained in the above-mentioned method for producing a laminate of the present invention.

[0096] <First thermal conductive layer> The first thermally conductive layer is preferably formed on and in contact with the silicon substrate. The first thermally conductive layer contains a condensation reaction product and a metal filler. The condensation reaction product and the metal filler can be appropriately selected from those described above in relation to the thermally conductive composition of the present invention.

[0097] The average thickness of the first thermally conductive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably 0.1 μm to 10 μm, more preferably 0.2 μm to 5 μm.

[0098] <Second heat conductive layer> The second thermally conductive layer contains a second hardening component, a second hardening agent, second thermally conductive particles, and low-melting point metal particles, and may further contain other components as required. The second curing component, the second curing agent, the second thermally conductive particles, and the low-melting point metal particles can be appropriately selected from those explained in the above-mentioned method for producing a laminate of the present invention.

[0099] The average thickness of the second thermally conductive layer is not particularly limited and can be appropriately selected depending on the purpose, but is preferably from 20 μm to 300 μm, and more preferably from 50 μm to 200 μm.

[0100] <Facing substrate> The opposing substrate is disposed opposite the substrate, and its shape, structure, size, material, etc. are not particularly limited and can be appropriately selected depending on the purpose. The shape of the opposing substrate may be, for example, a plate shape, a sheet shape, etc. The structure of the opposing substrate may be, for example, a single-layer structure, a laminated structure, etc. The size of the opposing substrate may be appropriately selected depending on the application, etc. The material of the facing base material is a material that is easily wetted by solder, and includes at least one selected from copper, gold, platinum, palladium, silver, zinc, iron, tin, nickel, magnesium, indium, and alloys thereof. The average thickness of the opposing substrate is not particularly limited and can be appropriately selected depending on the purpose. The opposing base material may be the heat spreader itself in the heat dissipation structure.

[0101] <Other materials> The other members are not particularly limited and can be appropriately selected depending on the purpose. For example, a protective layer can be mentioned.

[0102] Here, the laminate manufacturing method and the laminate according to the present invention will be described in detail with reference to the drawings. In each drawing, the same components are denoted by the same reference numerals, and duplicated descriptions may be omitted. In addition, the number, position, shape, etc. of the following components are not limited to the present embodiment, and may be any number, position, shape, etc. that is preferable for implementing the present invention.

[0103] FIG. 1 is a schematic view showing an example of a laminate according to the first embodiment. A laminate 10 shown in FIG. 1 has a first thermally conductive layer 12 formed on a silicon substrate 11 by applying a thermally conductive composition containing a condensation reaction product and a metal filler.

[0104] FIG. 2 is a schematic diagram showing an example of a process of a method for producing a laminate according to the second embodiment. The pre-cured laminate 20a shown in FIG. 2 is a pre-cured laminate after the first application step and the second application step and before the heating step, and specifically has a first thermally conductive layer 12 formed by applying a thermally conductive composition containing a condensation reaction product and a metal filler onto a silicon substrate 11, a second thermally conductive composition 14a containing second thermally conductive particles 14b and low-melting point metal particles 14c onto the first thermally conductive layer 12, and an opposing substrate 15 on the second thermally conductive composition 14a.

[0105] FIG. 3 is a schematic diagram showing an example of a laminate according to the second embodiment. The laminate 20 shown in FIG. 3 has a first thermally conductive layer 12 formed by applying a thermally conductive composition containing a condensation reaction product and a metal filler onto a silicon substrate 11, a second thermally conductive layer 14 containing second thermally conductive particles 14b and a low-melting point metal 14d onto the first thermally conductive layer 12, and an opposing substrate 15 onto the second thermally conductive layer 14.

[0106] The laminate of the present invention can be suitably used, for example, as a thermal interface material (TIM) that fills the minute gap between a heat source such as an LSI and a heat sink, thereby allowing heat to flow smoothly between the two, or when adhering a heat dissipation substrate mounting an LED chip or an IC chip to a heat sink to form a power LED module or a power IC module. Here, the power LED module is classified into a wire bonding mounting type and a flip chip mounting type, and the power IC module is classified into a wire bonding mounting type.

[0107] (heat dissipation structure) The heat dissipation structure of the present embodiment includes a heat generating body, the above-described laminate of the present invention, and a heat dissipation member, and further includes other members as necessary.

[0108] The heating element is not particularly limited and can be appropriately selected depending on the purpose. Examples of the heating element include electronic components such as a central processing unit (CPU), a micro processing unit (MPU), and a graphics processing unit (GPU).

[0109] The heat dissipation member is not particularly limited as long as it is a structure that dissipates heat generated by an electronic component (heat generating element), and can be appropriately selected depending on the purpose. Examples of the heat dissipation member include a heat spreader, a heat sink, a vapor chamber, and a heat pipe. The heat spreader is a member for efficiently transferring heat from the electronic component to other components. The material of the heat spreader is not particularly limited and can be appropriately selected depending on the purpose, and examples of the material include copper and aluminum. The heat spreader is usually in a flat plate shape. The heat sink is a member for releasing heat from the electronic component into the air. The material of the heat sink is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include copper and aluminum. The heat sink has, for example, a plurality of fins. The heat sink has, for example, a base portion and a plurality of fins provided so as to extend in a non-parallel direction (for example, a direction perpendicular to) one surface of the base portion. The heat spreader and the heat sink are generally solid structures with no internal voids. The vapor chamber is a hollow structure. A volatile liquid is sealed in the internal space of the hollow structure. Examples of the vapor chamber include a hollow structure of the heat spreader, a hollow plate-shaped structure of the heat sink, and the like. The heat pipe is a hollow structure having a cylindrical, approximately cylindrical, or flattened tubular shape, and a volatile liquid is sealed in the internal space of the hollow structure.

[0110] Here, Fig. 4 is a schematic cross-sectional view showing an example of a semiconductor device as a heat dissipation structure. The laminate 7 of the present invention dissipates heat generated by an electronic component 3 such as a semiconductor element, and is fixed to a main surface 2a of a heat spreader 2 facing the electronic component 3, as shown in Fig. 4, and is sandwiched between the electronic component 3 and the heat spreader 2. In addition, a thermally conductive sheet 1 is sandwiched between the heat spreader 2 and a heat sink 5.

[0111] The heat spreader 2 is formed, for example, in a rectangular plate shape, and has a main surface 2a facing the electronic component 3 and a side wall 2b erected along the outer periphery of the main surface 2a. The heat spreader 2 has a thermally conductive sheet 1 provided on the main surface 2a surrounded by the side wall 2b, and a heat sink 5 provided on the other surface 2c opposite the main surface 2a via the thermally conductive sheet 1. The higher the thermal conductivity of the heat spreader 2, the lower the thermal resistance and the more efficiently the heat is absorbed from the electronic component 3 such as a semiconductor element, so that the heat spreader 2 can be formed, for example, using copper or aluminum, which have good thermal conductivity.

[0112] The electronic component 3 is, for example, a semiconductor element such as a BGA, and is mounted on the wiring board 6. The tip surface of the side wall 2b of the heat spreader 2 is also mounted on the wiring board 6, so that the side wall 2b surrounds the electronic component 3 at a predetermined distance. By providing the laminate 7 of the present invention on the main surface 2a of the heat spreader 2, a heat dissipation member that absorbs heat generated by the electronic component 3 and dissipates the heat from the heat sink 5 is formed. EXAMPLES

[0113] Examples of the present invention will be described below, but the present invention is not limited to these examples.

[0114] <Preparation of Condensation Reactant 1> <<Preparation of partial hydrolyzate of alkyl silicate 1>> In a reaction vessel equipped with a nitrogen inlet tube, a thermometer, and a stirrer, methyl silicate represented by the general formula (1) (Methyl Silicate 51, manufactured by Colcoat Co., Ltd.; in the general formula (1), R 1= methyl group, n ≒ 4) 15 parts by mass of ethanol and 9 parts by mass of 0.01% by mass sulfuric acid were added to 100 parts by mass of the reaction mixture, and stirring was continued for another hour after the addition was completed. After the stirring was completed, an evaporator was used to distill off the methanol generated by hydrolysis and the added ethanol from the reaction mixture. The resulting distillation residue was passed through a cation exchange resin column to remove excess sulfuric acid. Stirring was continued for 10 hours while gradually adding 100 parts by mass of isopropyl alcohol to the resulting partial hydrolyzate. As a result, a partial hydrolyzate 1 of methyl silicate with a number average molecular weight of 350 was obtained as an isopropyl alcohol solution.

[0115] <<Preparation of Condensation Reactant 1>> In a reaction vessel equipped with a stirrer, 25 parts by mass (theoretical solid content 2% by mass) of the isopropyl alcohol solution of the prepared methyl silicate partial hydrolyzate 1 was added, and while stirring, a silane coupling agent represented by the general formula (2) (SILQUEST A-187, manufactured by Momentive Performance Materials Japan, LLC; in the general formula (2), R 2 = methyl group, Y = glycidoxy group, p = 0, q = 3) was gradually added to obtain condensation reaction product 1 as an isopropyl alcohol solution.

[0116] Example 1 <Preparation of first thermally conductive composition> To 80 parts by mass of the prepared condensation reaction product 1, 20 parts by mass of silver nanowire (T-YP808, manufactured by Seiko PMC Corporation, solid content 0.5% by mass) was added and mixed uniformly using a stirring device (Awatori Rentaro automatic orbital mixer, manufactured by Thinky Corporation) to prepare a first thermally conductive composition.

[0117] <Preparation of second thermally conductive composition> The composition and contents shown in Table 1 were mixed uniformly using a stirring device (Awatori Rentaro Automatic Orbital Mixer, manufactured by Thinky Corporation) to prepare a second thermally conductive composition. The content of each component in Table 1 is in volume percent.

[0118] <Production of the first laminate> Next, the first thermally conductive composition was applied to a substrate (silicon substrate) measuring 20 mm × 20 mm × 0.725 mm using a spin coater so that the average thickness after deposition was 0.5 μm to form a first thermally conductive layer, thereby producing the first laminate of Example 1.

[0119] <Production of the second laminate> Next, a second thermally conductive composition was applied onto the first laminate so that the average thickness after curing would be 100 μm, and a 20 mm x 20 mm x 1 mm opposing substrate (copper) was laminated on the second thermally conductive composition. The composition was then heated in two stages, at 150°C for 5 minutes and at 170°C for 60 minutes, and cured to form a second thermally conductive layer, thereby producing the second laminate of Example 1.

[0120] (Examples 2 to 3) The first laminate and the second laminate of Examples 2 to 3 were produced in the same manner as in Example 1, except that the condensation reaction product 1 in the first thermally conductive layer in Example 1 was replaced with condensation reaction product 1a and condensation reaction product 1b, which were prepared by the following procedure, respectively.

[0121] <Preparation of Condensation Reactant 1a and Condensation Reactant 1b> Condensation reaction products 1a and 1b were prepared in the same manner as in <Preparation of condensation reaction product 1>, except that the 25 parts by mass of the isopropyl alcohol solution of the partial hydrolyzate 1 of methyl silicate in <Preparation of condensation reaction product 1> was changed to 50 parts by mass and 100 parts by mass, respectively.

[0122] Example 4 The first laminate and the second laminate of Example 4 were produced in the same manner as in Example 1, except that the condensation reaction product 1 in the first thermally conductive layer in Example 1 was replaced with condensation reaction product 2 prepared by the following procedure.

[0123] <Preparation of Condensation Reactant 2> In the preparation of condensation product 1, the methyl silicate represented by the general formula (1) was converted into methyl silicate 51 (manufactured by Colcoat Co., Ltd.; 1= methyl group, n ≒ 4), to obtain methyl silicate 53A (manufactured by Colcoat Co., Ltd.; in the general formula (1), R 1 Condensation reaction product 2 was prepared in the same manner as in <Preparation of condensation reaction product 1>, except that n was changed to 1.5 (n = methyl group, n ≒ 7).

[0124] Example 5 A first laminate and a second laminate of Example 5 were produced in the same manner as in Example 1, except that the average thickness of the first thermally conductive layer in Example 1 was changed from 0.5 μm to 1.0 μm.

[0125] Comparative Example 1 The first and second laminates of Comparative Example 1 were manufactured in the same manner as in Example 1, except that in Example 1, the first thermally conductive layer was not formed and the second thermally conductive layer was formed directly on the substrate.

[0126] Next, for each of the obtained second laminates, "measurement of the average thickness of each layer," "thermal conductivity," and "adhesiveness" were evaluated as follows. The results are shown in Table 1.

[0127] <Measurement of the average thickness of each layer> Each second laminate was cut, the cut surface was polished, and the polished surface was photographed with a scanning electron microscope (S-3000N, manufactured by Hitachi, Ltd.). The thickness of each layer was measured from the cut surface of the laminate, and the average value of the thicknesses at any three points was calculated. The results are shown in Table 1. In the second laminate of Examples 1 to 5, it was confirmed that the first thermally conductive layer 12, the second thermally conductive layer 14, and the opposing substrate 15 were provided in this order on the silicon substrate 11, corresponding to the cross-sectional view of the laminate shown in Figure 3.

[0128] <Thermal conductivity> <<Preparation of laminated body after compression>> Each second laminate was sandwiched between a 20 mm x 20 mm square silicon plate (thickness 0.77 mm) and a 20 mm diameter copper plate (thickness 1.0 mm) and pressed for 5 minutes using a mini press under conditions of an upper plate temperature of 150°C on the copper substrate side, a lower plate temperature of 150°C on the silicon substrate side, and a set air pressure of 0.11 MPa (40 psi in terms of pressure).

[0129] <<Evaluation of thermal conductivity>> After bonding, the thermal resistance (℃ cm) of the laminate (interface Cu and silicon) was measured using a method in accordance with ASTM-D5470. 2 The thermal resistance of the laminate was calculated by subtracting the thermal resistance of the substrate (silicon substrate) and the opposing substrate (copper substrate) from the results, and the thermal resistance of the portion excluding the substrate and the opposing substrate from the laminate was calculated. The thermal conductivity (W / m K) was calculated from this thermal resistance and the thickness (100 μm) of the portion excluding the substrate and the opposing substrate from the laminate, and the thermal conductivity was evaluated according to the following criteria. [Evaluation Criteria] ◎: Thermal conductivity is 20 W / m K or higher. Good: Thermal conductivity is 10 W / m K or more and less than 20 W / m K. ×: Thermal conductivity is less than 10 W / m K.

[0130] <Adhesiveness> For each example, the adhesiveness of the laminate after compression bonding was evaluated according to the following procedure. The laminate after compression bonding was prepared according to the procedure explained in the above section on <Thermal Conductivity>. As a reliability test, a bond tester (4000Plus, manufactured by Nordson DAGE) was used to perform a shear test on the laminate after compression bonding under the test conditions of a shear rate of 200 μm, height of 150 μm, n=3, and an environment of 130°C, and the adhesion at high temperatures was evaluated. [Evaluation Criteria] ◯: The adhesive strength is 3 kg or more. ×: The adhesive strength is less than 3 kg.

[0131] [Table 1]

[0132] Details of each component in Table 1 are as follows.

[0133] -Curing component- Curing component (oxetane compound): ETERNACOLL (registered trademark) OXBP (manufactured by Ube Industries, Ltd.), 4,4'-bis[(3-ethyl-3-oxetanyl)methoxymethyl]biphenyl

[0134] - Hardener - Curing agent: a polyfunctional carboxylic acid represented by the general formula (I) (pentanedioic acid-1,1',1''-(1,2,3-propanetriyl) ester; molecular formula: C 18 H 26 O 12 ;Dexerials Corporation synthetic product)

[0135] -Low melting point metal particles (solder particles)- Sn 42 Bi 58 Manufactured by Mitsui Mining & Smelting Co., Ltd., Volume average particle size Dv: 4μm, Melting point 139℃ The volume average particle size Dv of the low-melting point metal particles is a value measured by a laser diffraction / scattering type particle size distribution measuring device (product name: Microtrac MT3300EXII).

[0136] -Second thermally conductive particle- Ag-coated Cu particles (D50: 10 μm): Ag-coated Cu particles, manufactured by Fukuda Metal Foil & Powder Co., Ltd., volume average particle size Dv: 10 μm The volume average particle size Dv of the metal filler is a value measured by a laser diffraction / scattering type particle size distribution measuring device (product name: Microtrac MT3300EXII).

[0137] -Thermoplastic resin- YP-50 (manufactured by Nippon Steel Chemical & Material Co., Ltd.), a polyhydroxypolyether synthesized from bisphenols and epichlorohydrin [Industrial Applicability]

[0138] The laminate of the present invention can achieve excellent heat resistance, thermal conductivity, and adhesion as a thermal interface material (TIM), and is therefore suitable for use in, for example, the vicinity of various electric devices such as CPUs, MPUs, power transistors, LEDs, and laser diodes, whose element operation efficiency, life span, and the like are adversely affected by temperature. [Explanation of symbols]

[0139] 1. Thermally conductive sheet 2 Heat spreader 2a Main surface 3 Heating elements (electronic components) 3a Top side 5. Heat sink 6 Wiring board 7 Laminate 10 Laminate 11 Silicon substrate 12 First heat conductive layer 14 Second heat conductive layer 14a Second thermally conductive composition 14b Second thermally conductive particles 14c Low melting point metal particles 14d Low melting point metals 15 Opposing substrate 20 Laminate 20a Laminate before curing

Claims

1. Contains a condensation reaction product and a metal filler, The thermally conductive composition is characterized in that the condensation reaction product is a condensation reaction product of a partial hydrolyzate obtained by partially hydrolyzing an alkyl silicate represented by the following general formula (1) and a coupling agent represented by the following general formula (2): 【Chemistry 1】 In the general formula (1), R 1 represents an alkyl group, and n represents a positive number. 【Chemistry 2】 In the general formula (2), R 2 represents an alkyl group, Y represents a substituent containing an epoxy group, p represents an integer of 0 to 3, and q represents a positive number.

2. R in the general formula (1) 1 The thermally conductive composition according to claim 1 , wherein is a methyl group or an ethyl group.

3. R in the general formula (2) 2 The thermally conductive composition according to claim 1 or 2, wherein is a methyl group or an ethyl group.

4. 3. The thermally conductive composition according to claim 1, wherein Y in the general formula (2) is a glycidoxy group.

5. The thermally conductive composition according to claim 1 , wherein the metal filler comprises at least one of silver nanowires, gold nanowires, copper nanowires, and aluminum nanowires.

6. A method for producing a laminate, comprising the step of applying the thermally conductive composition according to claim 1 onto a silicon substrate to form a first thermally conductive layer.

7. applying a second thermally conductive composition onto the first thermally conductive layer, the second thermally conductive composition including a second curing component, a second curing agent, a second thermally conductive particle, and a low melting point metal particle; The method for producing a laminate according to claim 6 , further comprising the step of heating the applied second thermally conductive composition.

8. A silicon substrate; A first thermally conductive layer provided on the silicon substrate, the first thermally conductive layer including a condensation reaction product and a metal filler; The laminate is characterized in that the condensation reaction product is a condensation reaction product of a partial hydrolyzate obtained by partially hydrolyzing an alkyl silicate represented by the following general formula (1) and a coupling agent represented by the following general formula (2): 【Chemistry 3】 In the general formula (1), R 1 represents an alkyl group, and n represents a positive number. 【Chemistry 4】 In the general formula (2), R 2 represents an alkyl group, Y represents a substituent containing an epoxy group, p represents an integer of 0 to 3, and q represents a positive number.

9. 9. The laminate of claim 8, further comprising a second thermally conductive layer disposed on the first thermally conductive layer, the second thermally conductive layer comprising a second curing component, a second curing agent, second thermally conductive particles, and a low melting point metal.

10. 10. The laminate according to claim 9, having a thermal conductivity of 30 W / (m·K) or more.

Citation Information

Patent Citations

  • Porous silver-made sheet and metallic member conjugate using the porous silver-made sheet

    JP2016169411A